Breeding field crops - Sleper, David Allen (Blackwell Pub., 2006)
Long recognized as the standard work in its field, this fifth edition of Breeding Field Crops deals with worldwide advances in plant breeding science and practice in recent years. Building on the foundations of earlier editions, this thoroughly revised volume includes expanded coverage on the role increased knowledge of genetics plays in the development of new crop cultivars, and fully explores exciting new developments in molecular biology. Breeding Field Crops, Fifth Edition, thoroughly covers the field of plant breeding. The latest edition of this venerable text provides a broad overview of the science of plant breeding, and provides students and breeders with essential fundamental information along with a review of current breakthroughs and technologies. This book will be a valuable source of information for anyone involved in the science of plant breeding for years to come.